Mechanical properties and fracture behavior of Al(111)/MgAlB4(0001) interface in Al matrix composites: a first-principle calculation study - Mingjie Wang; Yijie Zhang; Hongxing Zheng; Zhongyun Ru; Xiaoyu Yang (Materials Research Express, 2023)
Hexagonal crystal MgAlB _4 is a strengthening phase in Al matrix composites, which can significantly improve ultimate tensile strength. In this paper, the surface perform, interfacial bonding characteristic, fracture mechanism, and electronic properties of the Al(111)/MgAlB _4 (0001) interface were thoroughly investigated by the first principles method. The results reveal that the top-site and bridge-site configurations were more unstable than the hollow-site. Besides, from the calculated results of interfacial energy and work of adhesion, the hollow-stacked Al(111)/B(Al)-terminated/MgAlB _4 (0001) interface expresses stronger stability than other interfacial models, which is attributable to the higher work of adhesion and lower interfacial energy of the hollow-stacked Al(111)/B(Al)-terminated/MgAlB _4 (0001) interface. Analysis of electronic structure reveals that the Al-termination and Mg-termination Al(111)/MgAlB _4 (0001) interface presents Al-Al and Al-Mg metallic bonds at the interface, respectively, but the B(Al)-termination Al(111)/MgAlB _4 (0001) interface expresses strong Al-B covalent bonds characteristic, which leads to the highest interface stability. The results of tensile fracture revealed that the HCP stacked B(Al)-termination interface transferred the external stress to Al bulk, due to the Al-B covalent bond formed near the interface. Therefore, ceramic phase MgAlB _4 can effectively promote the particle reinforcement of Al matrix composites.